Analyzing Co-Occurrence of Non-Suicidal Self-Injury With Suicidal Ideation and Related Factors Among Adolescents in Jeju Island - Moon, Duk-Soo; Chung, Un-Sun; Kwack, Young Sook; Kim, Bung-Nyun; Kang, Na Ri (Journal of the Korean Academy of Child and Adolescent Psychiatry, 2024)
Non-suicidal self-injury (NSSI) and suicidal behavior, including suicidal ideation (SI) and suicide attempts, are important predictors of suicide in adolescents. This study aimed to investigate the associations between NSSI, SI, NSSI+SI, mental health problems, and family factors in Korean adolescents in Jeju Island, with an emphasis on key findings. A total of 561 adolescents completed self-report questionnaires regarding demographics, NSSI, SI, suicidal behavior, perceived family functioning, and mental health problems, which were assessed using Center for Epidemiological Studies Depression Scale for Children, Screen for Children Anxiety-Related Disorders (SCARED), and Youth Self-Report (YSR). Data were analyzed using descriptive statistics, one-way analysis of variance, chi-square test, post-hoc analyses, and multivariate logistic regression. In this study, 22.3% of adolescents reported either NSSI or SI, with 5.5% reporting NSSI and 20.7% reporting SI. Combined (NSSI+SI) group showed a significantly higher SCARED score, anxiety/depression, thought problems, attention problem, and rule breaking on YSR than did the SI only group. Higher level of depression and anxiety were significantly associated with NSSI and SI. Female sex and perceived family dissatisfaction were significantly associated factors for SI, but not for NSSI in multivariate logistic regression. This study provides insights into the clinical characteristics and associated factors among adolescents with NSSI, SI, and NSSI+SI in Jeju Island. Identifying these results can inform the development of targeted prevention and intervention strategies to mitigate the negative consequences of these behaviors and contribute to a better understanding of the role of family in this context.